Pengaruh Audit Partner Tenure dan Audit Firm Tenure terhadap Praktik Manajemen Laba pada Perusahaan Perbankan - Putri, Niken Estelita (Jurnal Akuntansi Kontemporer, 2012)
The financial statements are used to communicate financial information between stakeholders cause management to hide some information and sparked the management to do earnings management. To assess the fairness of financial statements, need an auditor. The length of an auditor assignment (audit partner tenure) and a public accountant firm (audit firm tenure) audited a company are feared would reduce the independence, objectivity, and the auditor's professional skepticism, which can increased earnings management. However, on the other hand, understanding client's business better enables auditor to detect the earnings management better. Therefore, this study examines the effect of audit partner tenure and audit firm tenure on earnings management in banking companies listed in Indonesia Stock Exchange. This quantitative research is conducted using audit partner tenure and audit firm tenure as the independent variables and earnings management as dependent variables. Data analysis was performed with multiple linear regression analysis. The data analysis indicated statistically insignificant result but in negative direction. It concluded that the longer audit partner tenure and audit firm tenure, it progressively decrease earnings management. This is because that a better understanding of the client's business will make auditor and accounting firm is enables to detect earnings management better.